2005
DOI: 10.1159/000087324
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Adult-Type Salivary Cortisol Circadian Rhythm in Hospitalized Preterm Infants

Abstract: Background/Aims: Knowledge of the presence or absence of cortisol (F) circadian rhythm in preterm infants is important for the interpretation of F measurements made in samples taken for both clinical and research purposes. Little is known about its emergence in very preterm infants. This study examines circadian rhythm in F secretion in hospitalized infants born before 30 weeks’ gestation. Methods: Design: Prospective longitudinal observational study. Subjects: 11 infants admitted consecutively and born before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…All samples were collected on the same day and not for the purpose of investigating CCR development. Viewing our results in relation to CCR development and comparing them with the diversity of approaches and results from earlier studies entailing a) infants at early age (<three weeks PNA) [69,71,73], b)…”
Section: Development Of Salivary Cortisol Circadian Rhythmmentioning
confidence: 79%
See 4 more Smart Citations
“…All samples were collected on the same day and not for the purpose of investigating CCR development. Viewing our results in relation to CCR development and comparing them with the diversity of approaches and results from earlier studies entailing a) infants at early age (<three weeks PNA) [69,71,73], b)…”
Section: Development Of Salivary Cortisol Circadian Rhythmmentioning
confidence: 79%
“…The primary focus was not necessarily on CCR development [64]. The results from studies on preterm infants were either in line with ours regarding time for onset of CCR [70,74], or the studies were not designed to cover that time period (one month CA) [68,69,[71][72][73]. De Weerth et al investigated the dynamics of cortisol levels among infants age nine months, with risk factors similar to our group of infants at high psychosocial risk, and concluded that high maternal stress predicts high infant cortisol levels with high total AUC; our findings of high variability in AUC along with CCR curves that do not flatten over time are consistent with these results.…”
Section: Development Of Salivary Cortisol Circadian Rhythmmentioning
confidence: 84%
See 3 more Smart Citations